ANALISIS GERAK SENI TARI PADA ANAK USIA SEKOLAH DASAR - Rena Elia; Farida Mayar; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Dance in the scope of educational space is very important as well as maintaining and preserving regional cultural arts, education and learning traditional arts in the elementary school environment is a place to maintain and cultural identity of the nation. Elementary school is one of the right places to introduce and develop the art of dance. The role includes students being able to express themselves according to their level of age and emotional development, so that learning becomes more interesting and exciting for students. This study used a literature study with the aim of determining dance movements in elementary school-age children.